Imunomodulação da resposta inflamatória induzida por infecção in vitro com cepa de Leishmania braziliensis resistente ao tratamento - Paiva, Yuri Tayro Carneiro Nóbrega (2023)
Leishmania braziliensis is the main etiological agent of cutaneous leishmaniasis (CL) in Brazil. Antimonials are the first-choice drugs for CL treatment; however, emerging reports of drug resistance have compromised the treatment and disease control. Studies on the initial inflamma- tory response induced by strains with a resistant profile are important to understand how these parasites evade the host’s protective response. The objective of this study was to compare the immune response of macrophages infected with strains of Leishmania braziliensis resistant (LbR) and susceptible (LbS) to meglumine antimoniate in vitro. Macrophages J774 (MJ774) were infected with LbR or LbS strains, and after 24, 48, and 72h, parasitic load, cytokine production (tumor necrosis factor [TNF-α], interleukin 12 [IL-12], interleukin 4 [IL-4] and interleukin 10 [IL-10]), as well as mediators of oxidative stress (nitric oxide [NO], malondialdehyde [MDA], catalase [CAT], superoxide dismutase [SOD] and reduced glutathione [GSH]) were evaluated. The results showed that MJ774 infected with LbR presented a significant increase in parasitic load at 48 and 72h compared to MJ774 infected with LbS, which, in turn, showed a significant decrease in parasitic load over time. At 24h post-infection, LbR induced an environment with higher levels of TNF-α, IL-12, IL-4, and CAT than that induced by LbS, which showed higher levels of only IL-10. At 48h post-infection, there was a shift of the environment with LbR infection, with lower levels of TNF-α and IL-12 and higher levels of IL-4, IL-10, and CAT. This is different from the environment with LbS, that showed a more inflammatory profile, with higher levels of IL-12, TNF-α, NO, and lower levels of IL-4, IL-10, and CAT. These inflammatory were environment still observed at 72h for both strains, except for SOD and NO levels which remained higher in the environment with LbS strain infection. In summary, the data from this study suggest that the resistant strain of L. braziliensis early on induces a more inflammatory environment than the susceptible strain. Later, it can transition to an immunologically permissive environment for its survival, maintaining a higher parasite load compared to the susceptible strain, and better withstanding the pressure of the microbicidal environment. This could hinder treatment efficacy, leading to prolonged disease persistence.